Protective Role of Hepatocyte Cyclooxygenase-2 Expression Against Liver Ischemia–Reperfusion Injury in Mice - Motiño García-Miguel, Omar (2019)
Liver ischemia and reperfusion injury (IRI) remains a serious clinical problem affecting liver transplantation outcomes. IRI causes up to 10% of early organ failure and predisposes to chronic rejection. Cyclooxygenase-2 (COX-2) is involved in different liver diseases, but the significance of COX-2 in IRI is a matter of controversy. This study was designed to elucidate the role of COX-2 induction in hepatocytes against liver IRI. In the present work, hepatocyte-specific COX-2 transgenic mice (hCOX-2-Tg) and their wild-type (Wt) littermates were subjected to IRI. hCOX-2-Tg mice exhibited lower grades of necrosis and inflammation than Wt mice, in part by reduced hepatic recruitment and infiltration of neutrophils, with a concomitant decrease in serum levels of proinflammatory cytokines. Moreover, hCOX-2-Tg mice showed a significant attenuation of the IRI-induced increase in oxidative stress and hepatic apoptosis, an increase in autophagic flux, and a decrease in endoplasmic reticulum stress compared to Wt mice. Interestingly, ischemic preconditioning of Wt mice resembles the beneficial effects observed in hCOX-2-Tg mice against IRI due to a preconditioning-derived increase in endogenous COX-2, which is mainly localized in hepatocytes. Furthermore, measurement of prostaglandin E2 (PGE2) levels in plasma from patients who underwent liver transplantation revealed a significantly positive correlation of PGE2 levels and graft function and an inverse correlation with the time of ischemia. Conclusion: These data support the view of a protective effect of hepatic COX-2 induction and the consequent rise of derived prostaglandins against IRI.